Indução do trabalho de parto em grávidas com cesariana anterior - Ana Rute Sousa Melo (2020)
The cesarean section rate has been increasing worldwide. As repeated cesarean sections have higher risks than a vaginal delivery, efforts are being made to increase the vaginal birth rates in women with previous cesarean section. However, there is a higher risk of uterine rupture among these women, and labor induction increases the risk even further. The factors influencing the success rate of vaginal birth after cesarean section were reviewed and a comparative analysis of the different methods of labor induction regarding success and uterine rupture rates was made. The purpose of this review is to assist in the selection of women who are better candidates for a trial of vaginal birth after cesarean as well as the safest and most effective method of labor induction in these women.